Sizing agent for electronic-grade glass fiber cloth and preparation method of sizing agent
By using a specific formula sizing agent and combined with the modification treatment technology, the electronic grade fiberglass fabric has been solved, and a higher quality electronic grade fiberglass fabric is achieved.
Patent Information
- Application Number
- CN202510057848.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing sizing agents used in electronic grade fiberglass cloths are difficult to effectively reduce the amount of hair while improving the mechanical properties and wear resistance, and the effect is not obvious.
A sizing agent composed of film forming agent, guar gum, emulsifier, additive, reinforcement, lubricant and deionized water is used to form a serous film with high strength and toughness through specific formulation ratios and preparation steps, and the dispersion of the reinforcement agent is improved through modification treatment.
It effectively reduces the hair volume of electronic grade fiberglass cloth, and significantly improves its mechanical properties and wear resistance, meeting the demand for high-quality substrates in copper clad manufacturing.
Smart Images

Figure BDA0005241950980000051 
Figure BDA0005241950980000061
Abstract
Description
Technical Field
[0001] The invention relates to a sizing agent, in particular to a sizing agent for electronic grade glass fiber cloth and a preparation method thereof. Background Art
[0002] Electronic grade glass fiber cloth is woven from electronic grade glass fiber yarn and is mainly used in the manufacture of copper clad laminates, which are special basic materials for printed circuit boards (PCBs). The quality of electronic grade glass fiber cloth is an important factor affecting the appearance quality of copper clad laminates, the processing performance of printed circuit boards, and the physical and chemical properties. With the development of printed circuit board manufacturing technology towards micro-aperture, fine lines, high-density wiring and high-multilayer, the requirements for substrate heat resistance, low expansion coefficient, high dimensional stability, low dielectric loss, etc. are also constantly improving. Therefore, the hairiness of electronic grade glass fiber cloth, the impregnation of resin, the strength and heat resistance of the board have become the focus of copper clad laminates.
[0003] Sizing is a key step in the glass fiber cloth processing process. This step is to coat the surface of the glass fiber cloth with a thin sizing film to improve the bundling performance between fibers, reduce the friction coefficient of the glass fiber monofilament surface, and enhance the mechanical and wear resistance of the glass fiber, making it more flexible and resistant to mechanical damage. The existing sizing agents used for electronic-grade glass fiber cloth have more or less some problems, including that the hairiness of the electronic-grade glass fiber cloth after sizing is still high, and the improvement effect on mechanical properties, wear resistance and other aspects is not obvious. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a sizing agent for electronic grade glass fiber cloth, which can effectively reduce the hairiness of the electronic grade glass fiber cloth and improve the mechanical properties and wear resistance of the electronic grade glass fiber cloth.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] A sizing agent for electronic grade glass fiber cloth is prepared from the following raw materials in parts by weight: 3-6 parts of a film former, 0.5-1 parts of guar gum, 0.6-0.9 parts of an emulsifier, 1-1.5 parts of an auxiliary agent, 1.5-2 parts of a reinforcing agent, 2-3 parts of a lubricant, and 82-85 parts of deionized water.
[0007] Furthermore, the film-forming agent of the present invention is composed of carboxymethyl starch and polyvinyl alcohol 17-99 in a weight ratio of 2:1.
[0008] Furthermore, the emulsifier of the present invention is dodecylphenol polyoxyethylene ether.
[0009] Furthermore, the auxiliary agent of the present invention is methyl glucose polyoxypropylene ether distearate.
[0010] Furthermore, the reinforcing agent of the present invention is prepared by the following steps:
[0011] (1) Add erbium oxide to deionized water, heat to 45° C., start stirring, add concentrated hydrochloric acid, and stir for 30 minutes to obtain an erbium chloride solution;
[0012] (2) dissolving tetradecanoic acid in deionized water, stirring for 10 minutes, then adding a sodium hydroxide aqueous solution, heating to 90° C. and continuing to stir for 20 minutes, adjusting the pH value to 7, then adding the erbium chloride solution obtained in step (1), continuing to stir at 90° C. for 2 hours, then standing and separating into an aqueous phase and an oil phase, discarding the aqueous phase, washing the oil phase with deionized water three times, and then filtering to obtain a filter cake, placing the filter cake in an oven and drying it to a constant weight to obtain a modifier;
[0013] (3) adding the modifier obtained in step (2) to an ethanol aqueous solution, stirring for 10 minutes to obtain a modifier solution, adding aluminum silicate to the modifier solution and continuing to stir for 12 hours to obtain a reaction solution, filtering the reaction solution to obtain a filter cake, washing the filter cake with deionized water and anhydrous ethanol for three times respectively, and then drying it in an oven to constant weight to obtain a reinforcing agent.
[0014] Furthermore, in step (1) of the present invention, the mass concentration of concentrated hydrochloric acid is 38%, the weight ratio of erbium oxide, deionized water and concentrated hydrochloric acid is 1:10:3, and the stirring speed is 200 rpm; in step (2), the mass concentration of sodium hydroxide aqueous solution is 0.5%, the weight ratio of tetradecanoic acid, deionized water, sodium hydroxide aqueous solution and erbium chloride solution obtained in step (1) is 1:10:12:3, the stirring speed is 400 rpm, and the drying temperature is 75°C; in step (3), the volume fraction of ethanol aqueous solution is 75%, the weight ratio of the modifier obtained in step (2), ethanol aqueous solution and aluminum silicate is 0.3:50:40, the stirring speed is 200 rpm, and the drying temperature is 75°C.
[0015] Furthermore, the lubricant of the present invention is polyethylene wax.
[0016] Another technical problem to be solved by the present invention is to provide a method for preparing the sizing agent for electronic grade glass fiber cloth.
[0017] To solve the above technical problems, the technical solution is:
[0018] A method for preparing a sizing agent for electronic grade glass fiber cloth comprises the following steps:
[0019] S1. Weigh the raw materials in parts by weight, add the film-forming agent and emulsifier to 1 / 4 weight of deionized water, and stir at 85-95 ° C for 12-18 hours to obtain a mixed slurry;
[0020] S2. The guar gum, additives, reinforcing agents and lubricants were added to the remaining deionized water and stirred for 50-60 minutes to obtain a mixture;
[0021] S3. Mix the mixed slurry obtained in step S1 and the mixed solution obtained in step S2, and stir for 30-40 minutes to obtain a sizing agent for electronic grade glass fiber cloth.
[0022] Furthermore, in steps S1, S2 and S3 of the present invention, the stirring speed is 200 rpm.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The film-forming agent used in the present invention is composed of carboxymethyl starch and polyvinyl alcohol, which has good film-forming properties. The formed size film has good strength and toughness, and the waste liquid generated during desizing has good biodegradability.
[0025] (2) Aluminum silicate is a reinforcing agent with good mechanical properties and wear resistance. However, there are polar functional groups such as hydroxyl groups on its surface, which leads to poor dispersibility in the sizing agent system. In this regard, the present invention first reacts erbium chloride with concentrated hydrochloric acid to obtain an erbium chloride solution, then conducts a coordination reaction between tetradecanoic acid and the erbium chloride solution to obtain a modifier, and then modifies the aluminum silicate with the modifier to obtain a reinforcing agent. The modifier has a strong complexing ability and can effectively eliminate polar functional groups such as hydroxyl groups on the surface of aluminum silicate, thereby reducing the polarity of the aluminum silicate surface and improving the dispersibility of aluminum silicate in the sizing agent system, thereby improving the mechanical properties and wear resistance of the electronic-grade glass fiber cloth after sizing.
[0026] (3) The present invention also uses methyl glucose polyoxypropylene ether distearate as an auxiliary agent, which can improve the dispersion and sizing effect of the sizing agent, thereby reducing the hairiness of the electronic-grade glass fiber cloth after sizing, and further improving the mechanical properties of the electronic-grade glass fiber cloth after sizing. DETAILED DESCRIPTION
[0027] The present invention will be described in detail below in conjunction with specific embodiments. The illustrative embodiments of the present invention and their descriptions are used to explain the present invention but are not intended to limit the present invention.
[0028] Example 1
[0029] The sizing agent for electronic grade glass fiber cloth is made of the following raw materials in parts by weight: 5 parts of film former, 0.8 parts of guar gum, 0.8 parts of emulsifier, 1.4 parts of auxiliary agent, 1.8 parts of reinforcing agent, 2.5 parts of lubricant, and 84 parts of deionized water. The film former is composed of carboxymethyl starch and polyvinyl alcohol 17-99 in a weight ratio of 2:1, the emulsifier is dodecylphenol polyoxyethylene ether, the auxiliary agent is methyl glucose polyoxypropylene ether distearate, the lubricant is polyethylene wax, and the reinforcing agent is made by the following steps:
[0030] (1) adding erbium oxide to deionized water, heating to 45° C., stirring, and adding concentrated hydrochloric acid with a mass concentration of 38%, wherein the weight ratio of erbium oxide, deionized water, and concentrated hydrochloric acid is 1:10:3, and stirring at 200 rpm for 30 minutes to obtain an erbium chloride solution;
[0031] (2) dissolving tetradecanoic acid in deionized water, stirring at 400 rpm for 10 minutes, adding a sodium hydroxide aqueous solution having a mass concentration of 0.5%, heating to 90° C. and continuing to stir for 20 minutes, adjusting the pH value to 7, and adding the erbium chloride solution obtained in step (1), wherein the weight ratio of tetradecanoic acid, deionized water, sodium hydroxide aqueous solution, and erbium chloride solution obtained in step (1) is 1:10:12:3, continuing to stir at 90° C. for 2 hours, standing and separating into an aqueous phase and an oil phase, discarding the aqueous phase, washing the oil phase with deionized water three times, and then filtering to obtain a filter cake, and drying the filter cake in an oven at 75° C. to constant weight to obtain a modifier;
[0032] (3) Adding the modifier obtained in step (2) into an ethanol aqueous solution with a volume fraction of 75%, stirring at a speed of 200 rpm for 10 minutes to obtain a modifier solution, adding aluminum silicate to the modifier solution and continuing to stir for 12 hours to obtain a reaction solution, wherein the weight ratio of the modifier obtained in step (2), the ethanol aqueous solution and the aluminum silicate is 0.3:50:40, filtering the reaction solution to obtain a filter cake, washing the filter cake with deionized water and anhydrous ethanol for 3 times respectively, and then drying it in an oven at 75° C. to constant weight to obtain a reinforcing agent.
[0033] The preparation method of Example 1 comprises the following steps:
[0034] S1. Weigh the raw materials in parts by weight, add the film-forming agent and emulsifier to 1 / 4 weight of deionized water, stir at 200 rpm and 90 ° C for 15 hours to obtain a mixed slurry;
[0035] S2. The guar gum, additives, reinforcing agents and lubricants were added to the remaining deionized water and stirred at 200 rpm for 55 minutes to obtain a mixture;
[0036] S3. The mixed slurry obtained in step S1 and the mixed solution obtained in step S2 are mixed, and stirred at 200 rpm for 35 minutes to obtain a sizing agent for electronic grade glass fiber cloth.
[0037] Example 2
[0038] The sizing agent for electronic grade glass fiber cloth is prepared from the following raw materials in parts by weight: 6 parts of film former, 1 part of guar gum, 0.9 parts of emulsifier, 1.5 parts of auxiliary agent, 1.6 parts of reinforcing agent, 2 parts of lubricant, and 85 parts of deionized water. The film former is composed of carboxymethyl starch and polyvinyl alcohol 17-99 in a weight ratio of 2:1, the emulsifier is dodecylphenol polyoxyethylene ether, the auxiliary agent is methyl glucose polyoxypropylene ether distearate, the lubricant is polyethylene wax, and the preparation steps of the reinforcing agent are the same as those in Example 1.
[0039] The preparation method of Example 2 comprises the following steps:
[0040] S1. Weigh the raw materials in parts by weight, add the film-forming agent and emulsifier to 1 / 4 weight of deionized water, stir at 200 rpm and 95 ° C for 12 hours to obtain a mixed slurry;
[0041] S2. The guar gum, additives, reinforcing agents and lubricants were added to the remaining deionized water and stirred at 200 rpm for 50 minutes to obtain a mixture;
[0042] S3. The mixed slurry obtained in step S1 and the mixed solution obtained in step S2 are mixed, and stirred at 200 rpm for 30 minutes to obtain a sizing agent for electronic grade glass fiber cloth.
[0043] Example 3
[0044] The sizing agent for electronic grade glass fiber cloth is prepared from the following raw materials in parts by weight: 4 parts of film former, 0.7 parts of guar gum, 0.7 parts of emulsifier, 1.2 parts of auxiliary agent, 2 parts of reinforcing agent, 3 parts of lubricant, and 83 parts of deionized water. The film former is composed of carboxymethyl starch and polyvinyl alcohol 17-99 in a weight ratio of 2:1, the emulsifier is dodecylphenol polyoxyethylene ether, the auxiliary agent is methyl glucose polyoxypropylene ether distearate, the lubricant is polyethylene wax, and the preparation steps of the reinforcing agent are the same as those in Example 1.
[0045] The preparation method of Example 3 comprises the following steps:
[0046] S1. Weigh the raw materials in parts by weight, add the film-forming agent and emulsifier to 1 / 4 weight of deionized water, stir at 200 rpm and 85 ° C for 18 hours to obtain a mixed slurry;
[0047] S2. The guar gum, additives, reinforcing agents and lubricants were added to the remaining deionized water and stirred at 200 rpm for 60 minutes to obtain a mixture;
[0048] S3. The mixed slurry obtained in step S1 and the mixed solution obtained in step S2 are mixed, and stirred at 200 rpm for 40 minutes to obtain a sizing agent for electronic grade glass fiber cloth.
[0049] Example 4
[0050] The sizing agent for electronic grade glass fiber cloth is prepared from the following raw materials in parts by weight: 3 parts of film former, 0.5 parts of guar gum, 0.6 parts of emulsifier, 1 part of auxiliary agent, 1.5 parts of reinforcing agent, 2.8 parts of lubricant, and 82 parts of deionized water. The film former is composed of carboxymethyl starch and polyvinyl alcohol 17-99 in a weight ratio of 2:1, the emulsifier is dodecylphenol polyoxyethylene ether, the auxiliary agent is methyl glucose polyoxypropylene ether distearate, the lubricant is polyethylene wax, and the preparation steps of the reinforcing agent are the same as those in Example 1.
[0051] The preparation method of Example 4 comprises the following steps:
[0052] S1. Weigh the raw materials in parts by weight, add the film-forming agent and emulsifier to 1 / 4 weight of deionized water, stir at 200 rpm and 92 ° C for 16 hours to obtain a mixed slurry;
[0053] S2. The guar gum, additives, reinforcing agents and lubricants were added to the remaining deionized water and stirred at 200 rpm for 56 minutes to obtain a mixture;
[0054] S3. The mixed slurry obtained in step S1 and the mixed solution obtained in step S2 are mixed, and stirred at 200 rpm for 32 minutes to obtain a sizing agent for electronic grade glass fiber cloth.
[0055] Comparative Example 1
[0056] The difference from Example 1 is that the raw materials do not include the auxiliary agent - methyl glucose polyoxypropylene ether distearate.
[0057] Comparative Example 2
[0058] The difference from Example 1 is that the reinforcing agent in the raw material is replaced by aluminum silicate, and the preparation step of the reinforcing agent is omitted.
[0059] Experimental Example 1: Mechanical Properties Test
[0060] The sizing agents prepared in Examples 1-4 and Comparative Examples 1-2 were added to the sizing device to perform sizing treatment on the electronic-grade glass fiber yarn, and then dried at 110°C to obtain electronic-grade glass fibers with a sizing film formed on the surface, and then the electronic-grade glass fibers were woven into electronic-grade glass fiber cloths. The breaking strength of each electronic-grade glass fiber cloth was tested using an electronic tensile testing machine with reference to JC / T996-2006. The higher the breaking strength, the better the mechanical properties. The test results are shown in Table 1:
[0061]
[0062]
[0063] Table 1
[0064] As can be seen from Table 1, the breaking strengths of Examples 1-4 of the present invention are all relatively high, indicating that the sizing agent prepared by the present invention can effectively improve the mechanical properties of electronic-grade glass fiber cloth. Some of the raw materials and preparation steps used in Comparative Examples 1-2 are different from those in Example 1. Compared with Example 1, the breaking strength of Comparative Example 1 is reduced, indicating that the auxiliary agent used in the present invention, methyl glucose polyoxypropylene ether distearate, can effectively improve the mechanical properties of electronic-grade glass fiber cloth; compared with Example 1, the breaking strength of Comparative Example 2 is also reduced, indicating that compared with aluminum silicate that has not been modified, the reinforcing agent prepared by the present invention has a better effect on improving the mechanical properties of electronic-grade glass fiber cloth.
[0065] Experimental Example 2: Wear resistance test
[0066] The abrasion resistance times of the electronic grade glass fiber cloths (Examples 1-4, Comparative Example 2) prepared in Experimental Example 1 were tested respectively with reference to ASTM D 3885-2004. The higher the abrasion resistance times, the better the abrasion resistance. The test results are shown in Table 2:
[0067] Wear times (times) Example 1 340 Example 2 320 Example 3 355 Example 4 310 Comparative Example 2 290
[0068] Table 2
[0069] As can be seen from Table 2, the wear times of Examples 1-4 of the present invention are all relatively high, indicating that the sizing agent prepared by the present invention can effectively improve the wear resistance of electronic-grade glass fiber cloth. Part of the raw materials and preparation steps used in Comparative Example 2 are different from those in Example 1. Compared with Example 1, the wear times of Comparative Example 2 are significantly reduced, indicating that compared with aluminum silicate that has not been modified, the reinforcing agent prepared by the present invention has a better effect on improving the wear resistance of electronic-grade glass fiber cloth.
[0070] Experimental Example 3: Hairiness Test
[0071] The hairiness of the electronic grade glass fiber cloths (Examples 1-4, Comparative Example 1) prepared in Experimental Example 1 was tested respectively with reference to FZ / T01086-2000. The test results are shown in Table 3:
[0072] Feather content (mg / 500m) Example 1 2.9 Example 2 3.3 Example 3 3.1 Example 4 3.6 Comparative Example 1 6.5
[0073] Table 3
[0074] As can be seen from Table 3, the hairiness of Examples 1-4 of the present invention is relatively small, indicating that the sizing agent prepared by the present invention can effectively reduce the hairiness of electronic-grade glass fiber cloth. Part of the raw materials used in Comparative Example 1 are different from those in Example 1. Compared with Example 1, the hairiness of Comparative Example 1 increases, indicating that the auxiliary agent used in the present invention, methyl glucose polyoxypropylene ether distearate, can effectively reduce the hairiness of electronic-grade glass fiber cloth.
[0075] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A sizing agent for electronic grade glass fiber cloth, characterized in that: The invention is prepared from the following raw materials in parts by weight: 3-6 parts of film former, 0.5-1 parts of guar gum, 0.6-0.9 parts of emulsifier, 1-1.5 parts of auxiliary agent, 1.5-2 parts of reinforcing agent, 2-3 parts of lubricant and 82-85 parts of deionized water.
2. The sizing agent for electronic grade glass fiber cloth according to claim 1, characterized in that: The film-forming agent consists of carboxymethyl starch and polyvinyl alcohol 17-99 in a weight ratio of 2:
1.
3. The sizing agent for electronic grade glass fiber cloth according to claim 1, characterized in that: The emulsifier is polyoxyethylene dodecylphenol ether.
4. The sizing agent for electronic grade glass fiber cloth according to claim 1, characterized in that: The auxiliary agent is methyl glucose polyoxypropylene ether distearate.
5. The sizing agent for electronic grade glass fiber cloth according to claim 1, characterized in that: The reinforcing agent is prepared by the following steps: (1) Add erbium oxide to deionized water, heat to 45° C., start stirring, add concentrated hydrochloric acid, and stir for 30 minutes to obtain an erbium chloride solution; (2) dissolving tetradecanoic acid in deionized water, stirring for 10 minutes, then adding a sodium hydroxide aqueous solution, heating to 90° C. and continuing to stir for 20 minutes, adjusting the pH value to 7, then adding the erbium chloride solution obtained in step (1), continuing to stir at 90° C. for 2 hours, then standing and separating into an aqueous phase and an oil phase, discarding the aqueous phase, washing the oil phase with deionized water three times, and then filtering to obtain a filter cake, placing the filter cake in an oven and drying it to a constant weight to obtain a modifier; (3) adding the modifier obtained in step (2) to an ethanol aqueous solution, stirring for 10 minutes to obtain a modifier solution, adding aluminum silicate to the modifier solution and continuing to stir for 12 hours to obtain a reaction solution, filtering the reaction solution to obtain a filter cake, washing the filter cake with deionized water and anhydrous ethanol for three times respectively, and then drying it in an oven to constant weight to obtain a reinforcing agent.
6. The sizing agent for electronic grade glass fiber cloth according to claim 5, characterized in that: In the step (1), the mass concentration of concentrated hydrochloric acid is 38%, the weight ratio of erbium oxide, deionized water and concentrated hydrochloric acid is 1:10:3, and the stirring speed is 200 rpm; in the step (2), the mass concentration of sodium hydroxide aqueous solution is 0.5%, the weight ratio of tetradecanoic acid, deionized water, sodium hydroxide aqueous solution and erbium chloride solution obtained in the step (1) is 1:10:12:3, the stirring speed is 400 rpm, and the drying temperature is 75°C; in the step (3), the volume fraction of ethanol aqueous solution is 75%, the weight ratio of the modifier obtained in the step (2), ethanol aqueous solution and aluminum silicate is 0.3:50:40, the stirring speed is 200 rpm, and the drying temperature is 75°C.
7. The sizing agent for electronic grade glass fiber cloth according to claim 1, characterized in that: The lubricant is polyethylene wax.
8. The method for preparing a sizing agent for electronic grade glass fiber cloth according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Weigh the raw materials in parts by weight, add the film-forming agent and emulsifier to 1 / 4 weight of deionized water, and stir at 85-95 ° C for 12-18 hours to obtain a mixed slurry; S2. The guar gum, additives, reinforcing agents and lubricants were added to the remaining deionized water and stirred for 50-60 minutes to obtain a mixture; S3. Mix the mixed slurry obtained in step S1 and the mixed solution obtained in step S2, and stir for 30-40 minutes to obtain a sizing agent for electronic grade glass fiber cloth.
9. The method for preparing a sizing agent for electronic grade glass fiber cloth according to claim 8, characterized in that: In the steps S1, S2 and S3, the stirring speed is 200 rpm.
Citation Information
Patent Citations
Production method for super-low-twisted electronic grade glass fiber cloth
CN102733033A
Glass fiber cloth sizing agent for prepreg and preparation method thereof
CN117247236A
Glass fiber-reinforced resin composition, and method for producing the same
JP2009215492A
Aqueous treating composition for glass fiber strands used to produce mats for thermoplastic polymers
US4369264A
Sizing agent for glass fibers
US4968776A